2022
DOI: 10.1007/s13202-022-01522-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and field application of biological nano-technology in the low- and medium-permeability reservoirs of an offshore oilfield

Abstract: As a result of deep burial depth, small pore throat, poor connectivity between pores, different clay mineral contents in reservoirs, and strong reservoir sensitivity, injection wells often have problems such as rapidly increasing water-injection pressure and insufficient water-injection quantity in the process of water-injection development. The main measures used to solve the difficulties of water injection in low-permeability reservoirs include fracturing, acidizing, and surfactant depressurization and injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…After being injected into the water injection well, it drives away the pore hydration film around the bottom of the well to increase the pore seepage area and form a hydrophobic film of nano-thickness, resulting in water phase slip to reduce the seepage resistance, thereby reducing the injection pressure of the water injection well. It has achieved very good results in the field pilot experiment in Bohai Oilfield. …”
Section: Introductionmentioning
confidence: 96%
“…After being injected into the water injection well, it drives away the pore hydration film around the bottom of the well to increase the pore seepage area and form a hydrophobic film of nano-thickness, resulting in water phase slip to reduce the seepage resistance, thereby reducing the injection pressure of the water injection well. It has achieved very good results in the field pilot experiment in Bohai Oilfield. …”
Section: Introductionmentioning
confidence: 96%
“…In a recent numerical simulation field, the E-amin research group has done some research on the transfer and mass transfer of nanoparticles in porous media and established a systematic flow coupling equation method of nanoparticles in porous media. Pryazhnikov and Guzei et al simulated the oil displacement process of nanoparticles from the micropore point of view, studied the flow characteristics of the oil displacement process of nanoparticles, and optimized the influencing factors of oil displacement by nanoparticles. However, there are still few reports about nanoparticles used in the field, and the numerical simulation of reservoir scale in this area is even rarer. , Therefore, most of these studies are still confined to laboratory tests or theoretical stages, and there is no verification of relevant field information reports.…”
Section: Introductionmentioning
confidence: 99%
“…37 − 40 However, there are still few reports about nanoparticles used in the field, and the numerical simulation of reservoir scale in this area is even rarer. 41 , 42 Therefore, most of these studies are still confined to laboratory tests or theoretical stages, and there is no verification of relevant field information reports.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the modified silica nanoparticles are adsorbed on the surface of the core and form a hydrophobic layer, changing the wettability of the sand surface from water wet to oil wet, thereby decreasing the flowing pressure. 18 Gao et al 19 established a set of biological nanomaterial depressurization and injection-augmenting numerical simulation technology water flooding models that consider the adsorption characteristics and reservoir physical properties. They also conducted a sensitivity analysis on the key injection parameters, drew the application effect prediction graph of the biological nanotechnology, and verified the model and prediction graph with actual oilfield data.…”
Section: Introductionmentioning
confidence: 99%